The Approach of Local Wisdom and Islamic Law to the Establishment of Regional Regulations on Alcoholic Drinks - HL, Rahmatiah; Arbani, Tri Suhendra; Damopolii, Muljono; M. Nur, Abdullah; Hanafiah, Muktar (Islamic Family Law Department, Sharia and Law Faculty, Universitas Islam Negeri Ar-Raniry, 2022)
In several regions in Indonesia, there are many criminal cases of abuse of alcoholic beverages, but on the other hand, in many regions, they provide legalization for alcoholic beverages themselves. The phenomenon of alcoholic beverages is faced with cultural connotations and local wisdom. From this view, this study will look at the influence of local wisdom and Islamic legal views so that they can influence local regulatory policies. Furthermore, the other hand, it will also discuss law enforcement from alcoholic beverages that have a terrible impact on the community. The research method used is a normative legal research method. The study uses a statutory approach and the analysis of legislation theory. The study results indicate that the traditions strongly influence the North Toraja area's formation of regional regulations in its community. One view can be drawn that the link between the traditions of a region will follow the existing regulations in that area. This is in line with the basis for the formation of regional regulations. There are three principal foundations: the philosophical, the juridical, and the sociological. The majority of the population in every Indonesian region is Muslim, which also affects the norm value of local government regulation. This can be seen in the Province of Aceh, which strongly opposes the existence of alcoholic beverages in the area. For the Province of South-Sulawesi alone in Takalar Regency, the same thing applies by strictly prohibiting the drinking, producing, and trading of alcoholic beverages, even though these include traditional drinks. Therefore, this research shows that strong Islamic values greatly influence the local community. Law enforcement is closely related to the implementation of sanctions from existing regulations. Penalty application is so religious in every area. Some impose sanctions regarding production and trade permits, and some apply criminal sanctions, and so on.